2023
DOI: 10.1001/jamanetworkopen.2023.17574
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Panax notoginseng Saponins in the Treatment of Adults With Ischemic Stroke in China

Abstract: ImportancePreclinical and clinical studies have suggested the neuroprotective effect of Panax notoginseng saponins (Xuesaitong soft capsules). However, robust evidence in patients with ischemic stroke is lacking.ObjectiveTo assess the efficacy and safety of Xuesaitong soft capsules in patients with ischemic stroke.Design, Setting, and ParticipantsThis multicenter, double-blind, placebo-controlled randomized clinical trial was conducted at 67 tertiary health centers in China from July 1, 2018, to June 30, 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Two studies ( Zhang et al, 2022 ; Wu et al, 2023 ) containing 3,162 cases reported all-cause mortality, whereas there was no significant difference between the XST group and the control group (RR = 0.43; 95% CI [0.06 to 2.93]; p = 0.39; I 2 = 0%) ( Figure 4 ). As such, no evidence was found to indicate that XST could reduce the all-cause mortality of AIS.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Two studies ( Zhang et al, 2022 ; Wu et al, 2023 ) containing 3,162 cases reported all-cause mortality, whereas there was no significant difference between the XST group and the control group (RR = 0.43; 95% CI [0.06 to 2.93]; p = 0.39; I 2 = 0%) ( Figure 4 ). As such, no evidence was found to indicate that XST could reduce the all-cause mortality of AIS.…”
Section: Resultsmentioning
confidence: 97%
“…We identified the overall bias as “low risk of bias” in one study ( Wu et al, 2023 ) and judged the remaining 45 studies to have a “high risk of bias”, indicating the poor quality of the selected RCTs. The results of the assessment of bias risk are presented in Figure 2 and Supplementary Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notoginsenoside R1 has been found to alleviate neuronal injury induced by β-amyloid through the inhibition of reactive oxygen species and regulating MAPK activation 48 . Study has shown that Panax notoginseng saponins significantly increase the probability of functional independence at 3 months in patients with IS, suggesting that this may be a safe and effective alternative treatment to improve the prognosis of this population 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The panax notoginseng saponins (PNSs) are extracted from the roots of Panax notoginseng (Burk.) F. H. Chen , and their main active ingredients include five components: ginsenoside Rg1 (Rg1), ginsenoside Rb1 (Rb1), ginsenoside Rd (Rd), ginsenoside Re (Re), and notoginsenoside R1 (R1) [ 3 , 4 ]. Extensive scientific research has shown that PNS has pharmacological activity, such as anti-inflammatory effects, angiogenesis promotion, thrombosis inhibition, and antioxidant properties [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%